Extracellular RNA in oncogenesis, metastasis and drug resistance - Hannah Nelson; Sherman Qu; Jeffrey L. Franklin; Qi Liu; Heather H. Pua; Kasey C. Vickers; Alissa M. Weaver; Robert J. Coffey; James G. Patton (RNA Biology)
Extracellular vesicles and nanoparticles (EVPs) are now recognized as a novel form of cell–cell communication. All cells release a wide array of heterogeneous EVPs with distinct protein, lipid, and RNA content, dependent on the pathophysiological state of the donor cell. The overall cargo content in EVPs is not equivalent to cellular levels, implying a regulated pathway for selection and export. In cancer, release and uptake of EVPs within the tumour microenvironment can influence growth, proliferation, invasiveness, and immune evasion. Secreted EVPs can also have distant, systemic effects that can promote metastasis. Here, we review current knowledge of EVP biogenesis and cargo selection with a focus on the role that extracellular RNA plays in oncogenesis and metastasis. Almost all subtypes of RNA have been identified in EVPs, with miRNAs being the best characterized. We review the roles of specific miRNAs that have been detected in EVPs and that play a role in oncogenesis and metastasis.